(untitled) (Medical Forum Monthly, 2020)
Objective: The study aims to identify impact of blended learning environment on self-directed learning skill development among post graduates of Masters in Health Professions Education. Study Design: Qualitative Study Place and Duration of Study: This study was conducted at Riphah International University from September 2019 to February 2020. Materials and Methods: Semi-structured interviews of all participants were audio recorded and transcribed verbatim. Later manual thematic analysis was performed to get meaning within the data. Results: Three major themes 1) Self-paced E learning, 2) motivation and satisfaction, 3) project-based teaching and learning were identified from ten sub-themes. The main factors like flexibility and convenience given to them in their learning, structured assessment policy, time management, self- pacing, more access to resources, and ease of communication have a major role to develop self-directed learning skill. Health professions Education is an emergent, interesting master degree program under blended learning environment that offers a great opportunity to be a lifelong learner to those who have completed their bachelor degree under traditional curriculum, in fact, most of the participants were rote learner are were not familiar to integration. Conclusion: Health Professions Education is an emergent Master degree program with pure blended learning environment, providing platform for health professionals to polish their soft and management capabilities through development of self-directed learning skill. This program enables the students to define and achieve their set goals within specific timeline. Infect, making students self-directed and lifelong learners in their continuing professional education.